2018
DOI: 10.3390/ijerph15020188
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitudes, Behaviors, and Barriers to School Readiness among Parents of Low-Income Latino Children

Abstract: We sought to explore parental attitudes, behaviors, and barriers regarding school readiness in a county clinic serving low income, Latino children. Between December 2013–September 2014, we conducted a cross sectional survey of parents during 3–6 years well-child appointments about school readiness (SR) across: (1) attitudes/behaviors; (2) barriers; and (3) awareness; and (4) use of local resources. Most parents (n = 210, response rate 95.6%) find it very important/important for their child to know specific ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 23 publications
4
32
0
4
Order By: Relevance
“…This interview, which takes 35 to 45 minutes to complete, has been utilized in low-income Latino populations. 16,40 The interview assesses (1) child SR; (2) parent SR-related attitudes and behaviors; (3) parent perception of SR-related barriers; and (4) parent awareness and use of local SR-related resources. This study utilized the parent SR-related behaviors and barriers portion of the interview:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This interview, which takes 35 to 45 minutes to complete, has been utilized in low-income Latino populations. 16,40 The interview assesses (1) child SR; (2) parent SR-related attitudes and behaviors; (3) parent perception of SR-related barriers; and (4) parent awareness and use of local SR-related resources. This study utilized the parent SR-related behaviors and barriers portion of the interview:…”
Section: Methodsmentioning
confidence: 99%
“…This was calculated based on a prior needs assessment that assessed parent SR behaviors and parent-reported barriers in the study population (eg, 55% of parents reported visiting the library with their child in 2014). 16…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ayrıca, anaokulu öğretmeninin dört yıllık eğitim veren okul öncesi lisans eğitimi almış olması, öğretmenlerin tecrübeli olması, okul öncesi eğitim yapılarında eğitim gören çocukların fiziksel özelliklerine uygun çevre koşulları oluşturulması beklenmektedir. Okul öncesi eğitim kurumlarının en önemli amacının çocukları ilkokula hazırlamak, çocukların öz-bakım becerilerini kazandırmak olduğunu ve çocuklara paylaşma, işbirliği gibi sosyal becerileri öğretmek olduğu da önem verilen konular arasındadır (Sevinç,2006;Tuğrul ve Tokuç,2007;Baran vd., 2007;Argon ve Akkaya,2008;Pianta ve arkadaşları, 2010;Topaç vd., 2012;, Kıldan, 2012;Rentzou, 2012;Şimşek ve İvrendi,2014;Özen Altınkaynak ve Yanıklar, 2014;Durualp vd., 2016;Polat Yaman ve Saçkes, 2017;Peterson et al ,2018) Bu çalışmada Eskişehir'de 0-6 yaş grubunda çocuğa sahip olan ailelerin kreş tercihleri ve kreşlerden beklentileri belirlenmeye çalışılmıştır. Ayrıca ailelerin demografik özelliklerinin, kreşlerden beklentileri üzerindeki etkisi de bu araştırmada ele alınan önemli unsurlardan biri olarak görülmektedir.…”
Section: Introductionunclassified